Fixed low-frequency broadband wireless access radio systems. - Danesh, M. (IEEE Communications magazine)
This article provides an overview of a fixed low-frequency broadband wireless access system for point-to-multipoint voice and data applications. The operating frequency bands are from 2 to 11 GHz, and the base station can use multiple sectors and will be capable of supporting smart antenna technology. The product system requirements, design of the radio subsystem specification, as well as an analysis of microwave transmission related to current radio technologies are presented. Examples of BWA technology are provided courtesy of Harris Corporation